Virantanaz – an epic in Vepsian? About the first attempt at an epic - Zaitseva, Nina (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2015)
The paper is a brief account of the events of the past 20 years, which have been essential for the fate of the Veps, and brought the author, who found herself in the very heart of the processes of Vepsian language and culture revival, to the idea of creating the epic. Can one create an epic in the language of a people (Vepsians in our case) whose memory has preserved no epic-style pieces of literature, no large oral literary forms, whose folklore heritage is not so rich, the nation itself is a minority, and its language is already red-listed? Or should one? Writing the work was a chance to retrieve from the people’s memory many facts, real or imaginary events, rituals, customs and legends, melodious idioms and sayings, which might help revitalise the people, its language and culture. The paper demonstrates the folklore and mythological background of the epic, represents and substantiates the key aspects of the style poetics, its folk heritage roots.